MANAGEMENT OF ACUTE TRAUMATIC INJURY WITH AYURVEDIC MEDICINES- A CASE STUDY ON ACUTE ROTATOR CUFF INJURY - Praveen P.P; Om Prakasah Dave; Dr. Praneetha Kesavan (The Bioscan, 2025)
PURPOSE Rotator cuff tear (RCT) is the most prevalent shoulder disorder, with asymptomatic RCT occurring in 20-25% of the general population and symptomatic tears affecting 30-40% of individuals over 60. Causes include injury, aging, degeneration, and reduced blood flow, leading to clinical features such as shoulder pain and restricted movement. In Ayurveda, RCT aligns with the concepts of vatavyadhi, apabahuka, and amsa marmabhighata, involving doshas like vata, pitha, raktha (acute stage), and kapha (later stage). Ayurvedic treatment consists of Samanam (curative) and Sodhana (purificatory) approaches, combining internal and external medications with strengthening exercises, yielding satisfactory outcomes particularly for mild to moderate tears. This case study details the successful Ayurvedic management of a 63-year-old female with a right rotator cuff injury from a fall, treated at Arya Vaidya Sala Salyatantra Vibhagam. METHODS Assessments were conducted on multiple days (Day 1, 7, 14, 17-21, 31, 62, 90) utilizing special tests (Drop Arm, Lag Sign, Lift-Off, Empty Can) to evaluate signs and symptoms. Tailored Ayurvedic interventions included internal and external medicines, focusing on pain (VAS) and range of motion (ROM). RESULTS Significant improvements were observed: range of motion increased from 300 to 1600 in goniometer measurement, and pain reduced from VAS score of 8 to 0-2 post-agnikarmam. Follow-up assessments every 15 days confirmed ongoing progress, leading to full Range Of Movments and minimal pain at 90 days. CONCLUSION This case report underscores the effectiveness of conservative Ayurvedic management in treating rotator cuff injuries, indicating a need for further studies to evaluate long-term outcomes.